Evaluation of economic feasibility of rooftop solar energy systems under multiple variables - Adekunle Olubowale Mofolasayo (Clean Technologies and Recycling)
Rooftop harvesting of solar energy is a promising method to provide a great portion of household energy requirements in many parts of the world. However, the cost of solar energy systems sometimes makes the exploration of rooftop solar energy systems not attractive to property owners. This study evaluates the economic factors that could affect the decision on whether to consider the installation of solar energy systems using the estimated time that the cumulative solar savings would become positive. The economic implication of increasing the micro-generation capacity of individual households, and the impact of varied interest rates, and subsidies were also evaluated. Among the three factors that were presented, the result showed that increasing the amount of electricity that is allowed to be generated from individual rooftops will result in the highest economic attractiveness for end-users. This is also expected to move the world closer to the goal of sustainable management of non-renewable resources for present and future generations. Increasing the micro-generation capacity of electricity from photovoltaic (PV) rooftops by individual households without increasing the electricity distribution fees results in a reduction of the time to reach positive solar savings. In addition, increasing the micro-generation capacity of electricity from PV rooftops is expected to contribute to a reduction in the greenhouse gas (GHG) emissions from the electricity grid for the entire community. This study recommends the encouragement of policies that allow for the maximization of electricity generation potential from rooftops of residential and industrial buildings.